4β-Hydroxycholesterol Signals From the Liver to Regulate Peripheral Cholesterol Transporters - Salonurmi, Tuire; Nabil, Heba; Ronkainen, Justiina; Hyötyläinen, Tuulia; Hautajärvi, Heidi; Savolainen, Markku J.; Tolonen, Ari; Orešič, Matej; Känsäkoski, Päivi; Rysä, Jaana; Hakkola, Jukka; Hukkanen, Janne (Frontiers in Pharmacology, 2020)
Activation of pregnane X receptor (PXR) elevates circulating 4β-hydroxycholesterol (4βHC), an agonist of liver X receptor (LXR). PXR may also regulate 25-hydroxycholesterol and 27-hydroxycholesterol. Our aim was to elucidate the roles of PXR and oxysterols in the regulation of cholesterol transporters. We measured oxysterols in serum of volunteers dosed with PXR agonist rifampicin 600 mg/day versus placebo for a week and analysed the expression of cholesterol transporters in mononuclear cells. The effect of 4βHC on the transport of cholesterol and the expression of cholesterol transporters was studied in human primary monocyte-derived macrophages and foam cells in vitro. The expression of cholesterol transporters was measured also in rat tissues after dosing with a PXR agonist. The levels of 4βHC were elevated while 25-hydroxycholesterol and 27-hydroxycholesterol remained unchanged in volunteers dosed with rifampicin. The expression of ATP binding cassette transporter A1 (ABCA1) was induced in human mononuclear cells in vivo. The influx of cholesterol was repressed by 4βHC, as was the expression of influx transporter lectin-like oxidized LDL receptor-1 in vitro. The cholesterol efflux and the expression of efflux transporters ABCA1 and ABCG1 were induced. The expression of inducible degrader of the LDL receptor was induced. In rats, PXR agonist increased circulating 4βHC and expression of LXR targets in peripheral tissues, especially ABCA1 and ABCG1 in heart. In conclusion, PXR activation-elevated 4βHC is a signalling molecule that represses cholesterol influx and induces efflux. The PXR-4βHC-LXR pathway could link the hepatic xenobiotic exposure an the regulation of cholesterol transport in peripheral tissues.